Distribution of Staphylococcus haemolyticus as the most dominant species among Staphylococcal infections at the Zainoel Abidin Hospital in Aceh, Indonesia - SUHARTONO; ZINATUL HAYATI; MAHMUDA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Suhartono S, Hayati Z, Mahmuda Mahmuda M. 2019. Distribution of Staphylococcus haemolyticus as the most dominant species among Staphylococcal infections at the Zainoel Abidin Hospital in Aceh, Indonesia. Biodiversitas 20: 2076-2080. The occurrence of Staphylococcus-related infections is emerging and might potentially harbor multidrug resistance leading to the major risks of hospital-associated infection. The study aimed to determine the dominant species distributed among Staphylococcus-related infections from clinical specimens and determine antibiotic resistance profile of the dominant species. The clinical samples were collected from inpatients and outpatients at the Zainoel Abidin Regional Hospital of Aceh, Indonesia during March 2017-March 2018. All clinical samples were mainly inoculated to plates containing blood agar followed by identification and determination of their antibiotic susceptibility using VITEK® 2 Compact. Statistical analysis was performed using Chi-square test or Fisher's exact test when appropriate to determine the independence of frequency distributions, and the tests were considered statistically significant at a P ? 0.05 on two-tailed. Of 693 Staphylococcus isolates found in the clinical specimens, Staphylococcus haemolyticus was the most predominant isolates with a total of 233 (32.2%), and it was identified with a high prevalence of methicillin-resistance (95.96%) termed as methicillin-resistant Staphylococcus haemolyticus (MRSH). MRSH were found in the blood samples and ICU patients accounting for 64.1% and 55.61%, respectively. The resistance profile of MRSH isolates exhibited a high level of resistance (more than 85%) to a wide range of antibiotics, including beta-lactams, (first to the fourth generation) cephalosporins, fluoroquinolones, carbapenems, and macrolides. This might be an alarming occurrence and require serious action to prevent MRSH dissemination of healthcare infections in the future.